Residue behavior and dietary risk assessment of fluopyram in cowpea and determination in nine foodstuffs - Ren, Saihao; Zhang, Yu; Zhang, Shanying; Lu, Hongwei; Liang, Xiaoyu; Wang, Lifeng; Wang, Meng; Zhang, Chenghui (Frontiers in Environmental Science, 2023)
Pesticide residues have been one of the food safety problems that plague consumers. It is necessary to develop validated detection methods to monitor pesticide residues in food. In this study, fluopyram was analyzed in fruits (banana, grape, citrus) and vegetables (tomato, cucumber, cowpea, pepper, eggplant and potato) by optimizing the QuEChERS in combination with GC-MS/MS. The recoveries of fluopyram in all food matrices ranged from 87.02% to 101.42% with RSD below 9.25 %. The matrix effect of fluopyram ranging from -1.41% to 17.67%. Finally, this market investigation resulted in a total of 19 positive samples out of 128 market samples, all of which fell below the MRL with the exception of one tomato sample, which was above the EU MRL. Field trial of fluopyram on cowpea was conducted, the half-lives of fluopyram was 3.03-3.95 d, terminal residues ranged from 0.031-0.596 mg/kg. Dietary risk assessment was performed on cowpea. The result indicates that the dietary risk of fluopyram in cowpeas is acceptable. The method of detection developed in this study could enable better monitoring of fluopyram residues in foodstuffs.